Lead identification and characterization of hTrkA type 2 inhibitors. Issue 22 (15th November 2019) - Subramanian, Govindan; Zhu, Yaqi; Bowen, Scott J.; Roush, Nicole; White, Julie A.; Huczek, Dennis; Zachary, Theresa; Javens, Christopher; Williams, Tracey; Janssen, Ann; Gonzales, Andrea
Abstract: Virtual in silico structure-guided modeling, followed by in vitro biochemical screening of a subset of commercially purchasable compound collection resulted in the identification of several human tropomyosin receptor kinase A (hTrkA) inhibitors that bind the orthosteric ATP site and exhibit binding preference for the inactive kinase conformation. The type 2 binding mode with the DFG-out and αC-helix out hTrkA kinase domain conformation was confirmed from X-ray crystallographic solution of a representative inhibitor analog, 1b . Additional hTrkA and hTrkB (selectivity) assays in recombinant cells, neurite outgrowth inhibition using rat PC12 cells, early ADME profiling, and preliminary pharmacokinetic evaluation in rodents guided the lead inhibitor progression in the discovery screening funnel. Graphical abstract: Unlabelled Image